Non-destructive prediction method of creep damage and remnant life related to those under creep–fatigue interactive conditions for nickel base superalloys. (May 2015) - Ando, A.; Toshimitsu Yokobori, A.; Sugiura, R.; Ohmi, T.; Ozeki, G.; Matsubara, T.
<x content-type="archive" xml:space="preserve">Abstract</x> In order to clarify the microdamage formation behaviour for high temperature brittle IN100 alloy, a polycrystalline nickel base superalloy, in situ observational test was carried out to observe creep damage formation behaviour of a notched IN100 specimen. Furthermore, the experimental findings of creep damage formation were evaluated by an original elastic–plastic creep finite element analysis. As a result, microcracks and damage forming areas were found to develop in the creep damage areas suggested by this analysis. This has resulted in the development of a non-destructive prediction method for creep damage accumulation and material's remnant life. The application of this method to the cases under creep–fatigue conditions was addressed.